PENGGUNAAN SAPAAN BAHASA ACEH DALAM KELUARGA PADA MASYARAKAT ACEH - Cut Irna Liyana (Prodi Sosiologi FISIP Universitas Teuku Umar, 2016)
This study aims to investigate and to describe the forms of address in family in Acehnese language that are used by Acehnese people. This study is qualitative research and descriptive method is used. This research is done by three stages of activity. The three of activities are data provision, data analysis, and result of research. Techniques that were used in data collecting of the forms of address in family of Acehnese people are through observation partipation and free interview with Acehnese people who are assumed know Acehnese language and custom well. The result of study shows that: 1) there are the differences of address term among some dialects in Aceh, such as North Aceh dialect, Aceh Pidie dialect, Great Aceh dialect, and West Aceh dialect. They are the addresses for father, mother, grandfather, grandmother, brother, sister, the old brother of father or mother, the old sister of father or mother, the young brother of father or mother, and the young sister of father or mother; 2) there is the interference of Arabic Language on the term of addresses in family of Acehnese language, such as the use of term abi, abon, waled, and abu for father; ummi, mi (from ummi), mu (from ummu) for mother, jiddon for grandfather, and jiddah for grandmother; 3) there are terms of addresess that are used only in certain people in society (nobility) such the use of address word ampon (ampon, ampon bang, ampon yah, ampon cek).Keywords: Form of Address, Term of Addresss in family, Acehnese people